Academic attitude and subjective norms effects on international doctoral students' academic performance self-perceptions: A moderated-mediation analysis of the influences of knowledge- seeking intentions and supervisor support. Issue 2 (30th April 2021) - Khuram, Waqas; Wang, Yanqing; Khan, Salim; Khalid, Aisha
Abstract : This study aimed to examine the relationship between international students' academic attitude and subjective norms on the one hand, and academic self-perception on the other hand in the context of student's perception of their knowledge- seeking intention and supervisor support. We gathered survey data from 415 international doctoral students from six top-tier universities in China (male = 61.4%; female= 38.6%; age range = 26 to 46 and above). The students were from the following regions: Asia 45.5%, Africa 40%, Europe 9.4 %, and America 5.1%. These students' majors were engineering and technology (39.8 %), business, management, and economics (33.7%), and social sciences (26.5 %). Moderated-mediated analysis indicated higher knowledge-seeking intention to mediate the relationship between students' academic attitude and subjective norms, and their academic performance self-perceptions. Higher self-rated supervisor support scores moderated the influences of academic attitude and subjective norms on the students' academic performance self-perceptions. Student development and support programs should seek to support international students' knowledge- seeking behaviours and supervisor access, enhancing their success with doctoral studies.